2022
DOI: 10.1111/jdv.18571
|View full text |Cite
|
Sign up to set email alerts
|

Rapid pruritus reduction with ruxolitinib cream treatment in patients with atopic dermatitis

Abstract: Background: Ruxolitinib cream is a topical formulation of ruxolitinib, a Janus kinase (JAK) 1/JAK2 inhibitor. Objectives:To report timing and magnitude of effect of ruxolitinib cream on itch in patients with atopic dermatitis (AD), a highly pruritic inflammatory skin disease. Methods: Two phase 3 trials (TRuE-AD1 [NCT03745638]/TRuE-AD2[NCT03745651]) enrolled patients aged ≥12 years with AD for ≥2 years, Investigator's Global Assessment score of 2 or 3, and 3%-20% affected body surface area. Patients (total N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…As previously reported, application of ruxolitinib cream resulted in early responses, with significant improvement in itch versus vehicle observed within 12 hours of first application, achievement of an itch‐free state as early as day 2, and considerable improvement in other endpoints, including IGA‐TS, observed at week 2 (first on‐treatment study visit) 10,23,24 . By week 8, more than half of patients achieved an IGA‐TS response 10 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…As previously reported, application of ruxolitinib cream resulted in early responses, with significant improvement in itch versus vehicle observed within 12 hours of first application, achievement of an itch‐free state as early as day 2, and considerable improvement in other endpoints, including IGA‐TS, observed at week 2 (first on‐treatment study visit) 10,23,24 . By week 8, more than half of patients achieved an IGA‐TS response 10 .…”
Section: Discussionsupporting
confidence: 52%
“…As previously reported, application of ruxolitinib cream resulted in early responses, with significant improvement in itch versus vehicle observed within 12 hours of first application, achievement of an itch-free state as early as day 2, and considerable improvement in other endpoints, including IGA-TS, observed at week 2 (first on-treatment study visit). 10,23,24 By week 8, more than half of patients achieved an IGA-TS response. 10 Among patients who did not achieve IGA-TS by week 8, responses were observed by other criteria, with >90% of patients in the ruxolitinib cream groups achieving a response by ≥1 measure at week 8, as reported in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A new substance already registered for vitiligo treatment namely ruxolitinib has been used topically in a double‐blind placebo‐controlled trial in atopic dermatitis. Significantly more patients achieved a reduction of itch by two or four points on a numerical rating scale compared to placebo (65% vs. 29%); the effects started already after 12 h 13 …”
Section: Allergy/eczemamentioning
confidence: 93%
“…A new substance already registered for vitiligo treatment namely ruxolitinib has been used topically in a double-blind placebo-controlled trial in atopic dermatitis. Significantly more patients achieved a reduction of itch by two or four points on a numerical rating scale compared to placebo (65% vs. 29%); the effects started already after 12 h. 13 In a study of 52 patients with Drug Reaction with Eosinophilia and Systemic Symptoms reactivation of human herpes virus was studied and found to occur at least with one episode in 77% of the patients, 53% showed two episodes of viral reactivation. Most commonly human herpes virus 6 (HHV-6) was involved and detectable in skin biopsies using non-coding transcripts of HHV-6 miR-aU14.…”
Section: A L L Ergy/ecz E M Amentioning
confidence: 99%
“…Ruxolitinib cream, a topical formulation of ruxolitinib, a potent, selective inhibitor of Janus kinase (JAK) 1 and JAK2, was first approved in the USA in 2021 for the treatment of patients ≥ 12 years old with mild to moderate AD [ 19 ]. US approval was based on results from the two pivotal phase 3 studies, which found monotherapy with ruxolitinib cream demonstrated significant and rapid reductions in signs and symptoms of AD [ 20 , 21 ]; long-term disease control was observed in the majority of patients with as-needed use [ 22 ]. Similar results were observed in a subset of patients with moderate and/or extensive disease at baseline [ 23 ].…”
Section: Introductionmentioning
confidence: 99%